Taking the CON out of Pennsylvania: Did Hip and Knee Replacement Patients Benefit? - Susan L. Averett; Sabrina Terrizzi; Yang Wang (Institute of Labor Economics (IZA), 2017)
Policymakers and the general public have expressed increasing concern over rising health care costs. The Certificate-of-Need (CON) programs began at the federal level in 1974 to stem the increase in costs by limiting hospital expansion and acquisition of equipment. The federal requirement for CON programs ended in 1987; however, 37 states and DC still maintain various forms of CON programs. We examine the effect of the expiration of Pennsylvania's CON law on indicators of quality and cost of health care for patients undergoing hip and knee replacement surgery. We use the standard difference-in-differences method and the Synthetic Control method. Our preferred method indicates that the expiration had no statistically significant effect on our various measures of quality and cost.
Keywords: I18; I10; 330; certificate of need; knee and hip replacement; health care; cost; quality